2022
DOI: 10.3390/neurolint14030057
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiological Characteristics for Recurrence of Chronic Subdural Hematoma: A Systematic Review and Meta-Analysis

Abstract: Chronic subdural hematoma (cSDH) is one of the most studied clinical entities in the neurosurgical literature. Management of cSDH is complicated by its propensity to recurrence. Various factors for the development of recurrence of cSDH have been described in various clinical, epidemiological, and observational studies, yet the evidence available is limited. A systematic review and meta-analysis as per PRISMA guidelines to identify clinical and radiological factors which can predict the development of recurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…We observed an acceptable reoperation rate (12.6 %) compared to a wide range of reported recurrence rates of 5–33 %. 3 , 7 , 8 , 9 , 10 However, the literature is heterogenous, as some studies report recurrence as reaccumulation requiring evacuation. According to Lakomkin et al, 3 the most common cause of readmission after CSDH evacuation was recurrent SDH (46.7 %).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed an acceptable reoperation rate (12.6 %) compared to a wide range of reported recurrence rates of 5–33 %. 3 , 7 , 8 , 9 , 10 However, the literature is heterogenous, as some studies report recurrence as reaccumulation requiring evacuation. According to Lakomkin et al, 3 the most common cause of readmission after CSDH evacuation was recurrent SDH (46.7 %).…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 The reported recurrence rates range from 5 % to 33 %. 3 , 7 , 8 , 9 , 10 Recurrence leads to a significant economic burden to the family and society. 11 Several studies have identified predictors for CSDH recurrence, usually with mixed results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median (interquartile range, IQR) patient sample size of the included studies was 93 (60-258). The median (IQR) recurrence rate of twenty-one studies (two studies did not provide recurrence data) was 17.5% (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Study and Population Characteristicsmentioning
confidence: 99%
“…In this context, previous studies have sought to establish the factors associated Diagnostics 2023, 13, 2449 2 of 13 with an increased risk of cSDH recurrence and/or which can aid in the prediction of neurological/functional outcomes. Thus far, several clinical factors, e.g., increased patient age, radiological characteristics, e.g., bilateral hematoma, and specific external membrane features, e.g., enhanced presence of angiogenic factors, have been previously indicated as risk factors for cSDH recurrence [5][6][7][8]. Additional research has focused on identifying prognostic molecular or cellular factors within the hematoma fluid and/or peripheral blood of cSDH patients.…”
Section: Introductionmentioning
confidence: 99%